Beauverdia, a resurrected genus of Amaryllidaceae (Allioideae, Gilliesieae) - Sassone, Agostina Belén (2014)
Based on morphological evidence, we resurrect the genus Beauverdia to include species of Ipheion section Hirtellum. All species now included in Beauverdia were also treated as part of Ipheion, Nothoscordum, or Tristagma. As here circumscribed, Beauverdia (Amaryllidaceae, Allioideae, Gilliesieae) is a South American genus that is found in Argentina, southern Brazil, and Uruguay. Two new combinations, Beauverdia dyalistemon (Guagl.) Sassone & Guagl., comb. nov. and Beaverdia hirtella var. lorentzii (Herter) Sassone & Guagl., comb. nov. are made, as well as descriptions, keys to related genera and species, lectotypes, and distribution maps.